DARI KAMPUS UNTUK DESA: KKN UNIVERSITAS KATOLIK SANTO THOMAS DI DESA DOLOK MARGU TAHUN 2025 - Jhonas Dongoran; Jontra Jusat Pangaribuan; Liana Liana; Yosuaris Harianja (ASOSIASI IDEBAHASA KEPRI, 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is a concrete implementation of the Tri Dharma of Higher Education in the field of community service, aiming to integrate academic learning with real social conditions in society. The 2025 KKN program of Universitas Katolik Santo Thomas was conducted in Dolok Margu Village, Lintong Nihuta District, Humbang Hasundutan Regency, under the theme “Serving, Devoting, and Sharing (BMB).” This program aimed to improve the quality of human resources and support village development through participatory and community empowerment approaches. The implementation method applied a participatory approach consisting of preparation, observation, planning, implementation, monitoring, and evaluation stages. The programs covered education, health, environmental care, and village institutional strengthening. The results indicate that the KKN activities had positive impacts on increasing children's learning motivation, community health awareness, environmental cleanliness, and the improvement of village administrative management and institutional capacity. In addition, the program contributed to the development of students’ character as social change agents. It can be concluded that the KKN program in Dolok Margu Village successfully strengthened synergy between higher education institutions and the community and provided tangible contributions to sustainable village development.